Enhancing Heat Transfer Using Multi-Size Teardrops obstacles (University of Thi-Qar Journal for Engineering Sciences, 2022)
In this paper, heat transfer enhancements using unique, various sets of teardrop-shapes inserts in a heating tube are numerically examined. The teardrop is a hemispheric placed on a conic part. The three-dimensional continuity, momentum and energy equations are repeatedly solved using ANSYS 17.1 software at turbulent flow regime with Reynolds number varies from 10000 to 30000. Nine cases are investigated excluding the plain tube case by changing the ratios of hemisphere diameter and conic part length to the tube diameter, dr and lr respectively. The tube was of diameter and length of 30 mm and 1000 mm respectively. The tested ratios were dr = 1/3, 1/2 and 2/3 while the ratio lr =5/3, 7.5/3 and 10/3. The results show that Nusselt number increases with increasing both dr and lr and vice versa because the greater dr interrupts the flow and therefore boosts swirling power in the tube. Similarly, the friction factor behaves as a consequence of the large blockage presence. However, the thermal performance factor TPF is less at the greatest dr and lr ratios, and the optimal one is obtained when the equipped teardrops were of dr=2/3 and lr=5/3 recording TPF=1.32 which is the most thermally efficient case among the rest. Over the empty tube, the percentage increase in TPF is 32% and 11% at Re=10000 and Re=30000 respectively. While the percentages in comparison with the smallest dr and lr are 11.8% at Re=10000 and 4.7% at Re=30000.